Peripartum Cardiomyopathy in Intensive Care Unit: An Update - Dinic, Vesna; Markovic, Danica; Savic, Nenad; Kutlesic, Marija; Jankovic, Radmilo J. (Frontiers in Medicine, 2015)
Peripartum cardiomyopathy (PPCM) is a systolic heart failure that occurs during the last month of pregnancy or within five months after delivery. It is uncommon disease of unknown ethiopatogenesis and very high rate of maternal mortality. Because of similarity between symptoms of PPCM and physiological discomforts during pregnancy, the early diagnosis of PPCM presents a major challenge. Since hemodynamic changes during PPCM can vitally jeopardise the mother and the fetus, patients with severe forms of PPCM require a multidisciplinary approach in intensive care units. This review summarize the current state of knowledge about the diagnosis, monitoring, and the treatment of PPCM. Having reviewed the recent researches it gives insight into the new treatment strategies of this rare disease.